ANALISIS DAMPAK KULIAH DARING MAHASISWA SAAT PASCA PANDEMI DAN PPKM TERHADAP MASYARAKAT UMKM KOTA MEDAN ( Studi Kasus Para Pengusaha Mikro di Kecamatan Medan Timur ) - Dewi Sundari; M. Guffar Harahap (KOLONI, 2022)
The government is taking steps in dealing with the threat from the Pandemic to save the nation's children. One of the steps taken is in the field of education by implementing online lectures for students in every university. Online learning activities and working from home for educators are changes that must be made by lecturers to continue teaching students. Distance education has the aim of improving the quality of education and the relevance of education as well as increasing equitable access and expansion of education. Distance education that is held with good quality assurance and in accordance with the needs of stakeholders is one of the mechanisms for expanding access to higher education. This study aims to determine the impact of student online lectures on the MSME community in Medan City (object of research for Micro and Small Entrepreneurs in East Medan District). Based on the results of the research conducted, it can be concluded that online learning applied to students must be carried out alternately by providing time lapses or changing times, meaning that online lectures are carried out by inserting face-to-face lectures, for example the first week face-to-face then the second week of lectures again online and and so on for the following week by always implementing health protocols and maintaining distance and dividing face-to-face time for 2 meetings each class in turn. The presence of campus students, although not entirely every week, will bring changes to the community of MSME actors who work around campus and depend on students as consumers who can mainly help their income, which during the Post-Pandemic period and PKKM greatly decreased, it will increase even though it is not optimal. With this change, the MSME community around the campus can maintain their business and avoid their business from experiencing a situation that is in danger of closing. Keywords: Online, UMKM, Post Pandemic and PPKM